Implementation of Programmed Intermittent Epidural Bolus for the Maintenance of Labor Analgesia. (October 2016) - Carvalho, Brendan; George, Ronald B.; Cobb, Benjamin; McKenzie, Christine; Riley, Edward T.
Abstract : Programmed intermittent epidural bolus (PIEB) is an exciting new technology that has the potential to improve the maintenance of epidural labor analgesia. PIEB compared with a continuous epidural infusion (CEI) has the potential advantage of greater spread within the epidural space and therefore better sensory blockade. Studies have demonstrated a local anesthetic–sparing effect, fewer instrumental vaginal deliveries, less motor blockade, and improvements in maternal satisfaction with PIEB compared with CEI. However, the optimal PIEB regimen and pump settings remain unknown, and there are a number of logistical issues and practical considerations that should be considered when implementing PIEB. The PIEB bolus size and interval, PIEB start time delay period, and patient-controlled epidural analgesia bolus size and lockout time can influence the efficacy of PIEB used for epidural labor analgesia. Educating all members of the health care team is critical to the success of the technique. This review summarizes the role of PIEB for the maintenance of labor analgesia, outlines implementation strategies, suggests optimal settings, and presents potential limitations of the technique. Abstract : Supplemental Digital Content is available in the text.Published ahead of print July 26, 2016.